El principio de igualdad y proporcionalidad en la suspensión condicional de la pena - Arroyo Haro, GustavoAlejandro (2024)
ABSTRACT: The present research delves into a detailed analysis of the legal and doctrinal principles of equality and proportionality in the criminal context, with a particular focus on their application to the institution of conditional suspension of sentence within Ecuador's legal framework. The relevance of considering the specific circumstances of each individual and the particular sentence imposed in determining his or her eligibility for conditional suspension is highlighted, raising significant questions about the validity of a requirement that relies exclusively on the sentence in the abstract. It is argued that this practice may give rise to possible infringements of the principles of equality and proportionality, especially in cases involving degrees of participation, effective collaboration, aggravating and mitigating factors. A critical and exhaustive analysis of these aspects in the Ecuadorian criminal justice system is carried out and argues for the need to adopt a more equitable and proportional approach in the implementation of conditional suspension of sentences. In addition, it explores fundamental issues related to unconstitutionality and the implications for those individuals whose circumstances and levels of collaboration do not adequately conform to the current legislation, highlighting the importance of a legal reform that more precisely adapts to the principle of proportionality and the right to formal and material equality.